Risk of nutritional status on diarrhea among under five children - Wiliam Jayadi Iskandar; I wayan Sukardi; Yati Soenarto (Indonesian Pediatric Society, 2015)
Background Diarrhea is still the leading cause of children’s mortality worldwide and the main cause of malnutrition. Meanwhile, malnourished children are proven to have more severe, prolonged, and frequent episodes of diarrhea, making them a vicious circle.Objective To investigate the risk of nutritional status on diarrheal severity and duration as well as length of hospital stay.Methods We conducted a cross sectional study involving 176 under five children who admitted to Mataram Province Hospital with acute diarrhea since January until December 2013. We analyzed data using logistic regression model.Results Most subjects were infants (median 12 months, range 1-53), male (56.8%), well-nourished (85.8%), admitted with acute watery diarrhea (97.2%), mild-to-moderate dehydration (71.6%), diarrhea severity score ≥11 (74.4%), duration of diarrhea ≤7 days (96.6%), and length of stay <5 days (73.3%). Logistic regression model indicated significant risk of nutritional status on length of hospital stay (adjusted OR 2.09, 95% CI 1.06 to 6.38), but neither diarrheal severity (adjusted OR 1.03, 95% CI 0.38 to 2.80) nor duration of diarrhea (adjusted OR = 1.17, 95% CI = 0.13 to 10.89) indicated significant risks. However, malnourished children had more severe (76% versus 74.2%) and longer duration (4% versus 3.3%) of diarrhea than well-nourished children.Conclusion Nutritional status is the risk for length of hospital stay in under-five children admitted with acute diarrhea. [